DETEKSI DAN QUANTIFIKASI BAKTERI PENGHASIL ENZIM FITASE DI SALURAN PENCERNAAN IKAN NILA (Oreochromis niloticus) - Muhamad Amin; Mita Ayu Lilianti; Juwaidin Juwaidin; Husnawati Husnawati; Hasnah Hasnah (Jurnal Perikanan Unram, 2018)
Phytate content which is considered as anti-nutritional factors has been frequently associated with plant-based diets. One way to dealt with this issue is by supplementation of exogenous phytase-producing bacteria. Thus, this study was aimed at detection and quantification of phytase-producing bacteria from the gastrointestinal tract of cultured Nile tilapia (Oreochromis niloticus) and wild tilapia. The result showed that phytase-producing bacteria were only detected from the gastrointestinal tract of cultured tilapia, while none was observed from the wild tilapia. Total viable count (TVC) of bacteria associated with the gastrointestinal tract of cultured Tilapia was recorded at 7.8 x 107 CFU/g, and the number of phytase-producing bacteria were counted for 2.6 x 106 CFU/g or about 3.31%. This research result indicated the presence of phytase-producing bacteria in the gastrointestinal tract of Nile tilapia. However, further research is still required to quantify the amount and activity of phytase in the intestinal tract of the fish. In addition, those phytase-producing bacteria should be identified in order to track where the bacteria came from.